AB0030 Persistence of Humoral and Cellular Immunity Against Tick-Borne-Encephalitis Vaccination in Patients with Juvenile Idiopathic Arthritis (JIA). (9th June 2015) - Robrade, K.; Stern, R.; Almanzar, G.; Kleines, M.; Speth, F.; Hügle, B.; Haas, J.P.; Prelog, M.
Abstract : Background: Reduced immunogenicity and efficacy of vaccinations and waning of vaccine-antigen-specific immunity were reported for patients with rheumatic diseases with immunosuppressive therapy or biologics. So far, the persistence of the humoral and cellular immune response against tick-born-encephalitis-virus (TBEV) vaccine was not analyzed in immunocompromised patients with Juvenile Idiopathic Arthritis (JIA). Objectives: Thus, the TBEV-specific humoral and cellular immunity was investigated in 64 patients with JIA and 38 age-matched healthy controls who had received at least three dosages of TBEV-vaccine in the past. Methods: Antibody concentrations and avidities were measured by adapted ELISAs, TBEV-specific cellular reactivity by ELISPOT assays in spot forming units (SFUs) per 100.000 cells. Results: Positive IgG-anti-TBEV antibody concentrations (>165 VIEU/ml) were found in 59 JIA patients (92.2%) compared to 100% of healthy controls. Forty-one JIA patients (64.1%) had high antibody concentrations >1000 VIEU/ml compared to 34 HC (89.5%). Relative avidity index (RAI) was high in JIA patients (82.9%). Significantly higher SFUs were seen in HC (mean 780 SFU) than in JIA (500 SFU). So far, no correlations between TBEV-specific antibody concentrations, avidities or SFU were found. Conclusions: Although lower TBEV-specific antibody concentrations and SFU were demonstrated by JIA patients, a sufficient TBEV-specific humoral and cellular immune response was presented even several years after primary TBEV-vaccination in those patients. Whether TBEV-specific immunity may be influenced by age, therapeutic regimens and disease activity and will wane faster in JIA patients with need for earlier booster doses requires proof by longitudinal studies. Disclosure of Interest: None declared